FIRE EMERGENCY RESPONSE PLANNING IN THE STUDIO Y AT TELEVISION STATION X WEST JAKARTA - Kusumohadi, Catur Setyawan; Farida, Fransisca Maria; Prawesti, Eufrasia Viany (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
As a prevention as most fires occur in building, it is important to plan a fire emergency. This study aims to make a fire emergency response plan in Studio Y at Television Station X. Data collection was carried out at Studio Y by identifying potential fire hazards and analyzing emergency response facilities and infrastructure. The results showed that Studio Y had a fairly high fire hazard potential because there were many tools and equipment that could be triggering a fire. Therefore, planning for a fire emergency was carried out according to the fire scenario and determining evacuation routes which were divided based on color zones and the number of available doors.